Efficacy of Antihistamine Nasal Spray Compared with Oral Antihistamine in Treatment of Allergic Rhinitis - Jawad Ahmad, Najaf Abbas, Mazhar Iftikhar, Shahbaz Mujtabaghauri, Mohammad Qamar Nasir (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Allergic rhinitis is described as nasal membrane inflammation and is characterized by a symptom complex of sneezing, nasal congestion, itching, and rhinorrhea. These structures are also involved to some extent due to the continuity of the mucosal wall of the nose with the paranasal sinus and its communication with the ears through the Eustachian tube and with the eyes with the nasolacrimal duct. Objective: To determine the efficacy of antihistamine nasal spray compared with oral antihistamine in treatment of allergic rhinitis. Method: This Randomized control trial was conducted at the ENT department, Services Hospital, Lahore for 18 months from 01-02-2020 to 31-08-2022. Sample 450 patients of Allergic rhinitis of both sexes between the ages of 15-50 years were selected using simple random sampling technique. Patients were divided into 2 groups. Group A received oral antihistamine ebastine 10mg OD whereas Group B received nasal antihistamine spray olopatadine 0.6% (600mcg/100microlitre). Patients were then followed up every 2 weeks for 01 month. Data was enetered and analyzed in SPSS. Results: Total 450 patients were enrolled. The mean age was 24.5+ 3.0 years. There were 270(60%) male and 180(40%) female. In group A, there were 72(32%) patients 10 to 30 years of age group and 153(68%) were 30 to 50 years of age group. In group B, 65(28.8%) patients between 10 to 30 years and 160(71.1%) above 30 years of age group. Table: 2 In our study, sneezing was the most common 441(98%) followed by rhinorrhea 427(94.8%), nasal obstruction 338(75.1%), etc…In Group A, 153(68%) patients got relief and 72(32.0%) patients felt decrease in symptoms of Allergic rhinitis. In Group B, 144(64.0%) patients got relieved of symptoms, 81(36.0%) patients were partially relieved. Conclusion: The conclusion of the study that oral antihistamine and intranasal antihistamine nasal spray proved that treatment results of both treatment options were comparable in terms of reduction in the symptoms of allergic rhinitis. AIM: Our aim of the research is to determine the efficacy of antihistamine nasal spray compared with oral anti histamines in the treatment of allergic rhinitis. The sedating effects of oral antihistamines can totally be avoided in case nasal sprays have the same efficacy. Keywords: Allergic rhinitis, Antihistamine, Seasonal allergic rhinitis,